Recombinant Mycobacterium bovis BCG is a promising platform to develop vaccines against Trypansoma cruzi infection. (6th July 2020) - Bontempi, I.; Leal, K.; Prochetto, E.; Díaz, G.; Cabrera, G.; Bortolotti, A.; Morbidoni, H. R.; Borsuk, S.; Dellagostin, O.; Marcipar, I.
Summary: Chagas disease, caused by the hemoflagelate parasite Trypanosoma cruzi, is one of the most prevalent endemic parasitoses, affecting 7–8 million people. Due to the complexity of the infection, no vaccines are available at present. The extraordinary adjuvant capacity of bacille Calmette–Guérin (BCG) was explored in this work to develop a vaccine candidate to protect against T. cruzi infection using the recombinant BCG (rBCG) vaccine platform. Three antigens of the parasite corresponding to the N and C terminal fragments of the enzyme trans‐sialidase (NT‐TS and CT‐TS, respectively) and a fragment of the cruzipain enzyme (CZf) were cloned into the vectors pUS997 and pUS2000 and transformed into the BCG Pasteur strain. In vaccinated mice, rBCG expressing NT‐TS in pUS2000 plasmid provided the highest protection and the lowest parasitemia after challenging BALB/c mice with a 50% lethal dose of parasites. When mice vaccinated with pUS2000‐NT‐TS were challenged with a 100% lethal dose of parasite, high levels of protection were also obtained, together with a low degree of cardiac lesions 120 days after infection. In immunized mice with pUS2000‐NT‐TS/rBCG clone, the proliferation of CD4 + cells from splenocytes stimulated with the TS antigen was significant; this stimulation increased interferon (IFN)‐γ and interleukin (IL)‐17 within CD4⁺ T lymphocytes (LTCD4 + ) cells and IFN‐γ and CD107 expression within LTCD8 + cells. Therefore, pUS2000‐NT‐TS/rBCG conferred high levels of protection, which correlated with an immune response orientated towards a T helper type 1 (Th1)/Th17 profile, together with an LTC‐specific response, indicating that rBCG is a promising platform to develop vaccines against T. cruzi . Abstract : The use of the recombinant BCG vaccine platform to protect against T. cruzi infection is described. Six constructions of rBCG were obtained and assessed in a mice model of the infection. Mice vaccinated with rBCG expressing N terminal fraction of TS antigen presented the best protection. Also the vaccine protects against the development of cardiac lesions characteristic of the T cruzi infection in the chronic phase of the infection. The use of recombinant BCG vaccine against T cruzi allow a LTC, TH1 and TH17 cellular response that is needed to fight the parasite in accord by previous reports.